Children who survive torture: A systematic review of screening, documentation and treatment of torture injuries in children - Catarina Nahlén Bose; Ronak Tamdjidi (Torture)
Background: Children all over the world are subjected to torture, but few are identified as victims of these actions. Knowledge that facilitates identification, documentation, and treatment of torture injuries in children can allow redress and rehabilitation for more children in need. Objective: To synthesise research regarding screening, documentation, and treatment of child survivors of torture. Methods: A systematic literature review was conducted. A total of 4795 titles and/or abstracts were screened, of which 80 articles were included. Grey literature was also included. Results: Screening for torture exposure usually consisted of questions that were included in trauma questionnaires. Questions about perpetrators in the traumatic events were missing from more than half of the studies. Although children were screened mainly for psychological injuries, it was primarily physical injuries that were documented. The evidence on treatment effects was limited. However, there was a tendency that Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) and Narrative Exposure Therapy (NET) significantly reduced PTSD up to three months to one year after the end of treatment. Treatments with individual and group-based formats, as well as those with normal and more intensified approaches, were found to have an effect on PTSD.